PENGARUH KEPEMIMPINAN DISTRIBUTIF, TEAM WORKING , DAN KEPUASAN KERJA TERHADAP KINERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH SUMBAWA NUSA TENGGARA BARAT - Andi Rusni; Ary Sutrischastini (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2020)
Health is a right that must be given by the state to each of its citizens. This has been stated in the 1945 Constitution and Law Number 36 Year 2009 Concerning Health. Nurses as Health Workers in the Hospital become an important factor in supporting optimal health services for patients. The purpose of this study was to analyze both partial and simultaneous influence of distributive leadership, teamwork and job satisfaction on the performance of nurses in RSUD Sumbawa NTB. This study uses quantitative survey methods. The survey was conducted with a questionnaire of 137 nurses in RSUD Sumbawa NTB. Data analysis techniques used are simple regression analysis and multiple regression.The results showed that 1.) Leadership had a positive and significant effect on the performance of nurses in Sumbawa NTB Regional Hospital, 2.) The team worked positively and significantly on the performance of nurses in RSUD Sumbawa NTB, 3.) Positive and significant job satisfaction on Nurse Performance in RSUD Sumbawa NTB, and 4) Simultaneously distributive leadership, teamwork and job satisfaction are significant to the performance of nurses in RSUD Sumbawa NTB.